Review on 6G communication network technology for sustainable renewable energy system: implementations, constraints, and recommendations - Abdur, Rashid; Parag, Biswas; Ahasan Habib, AKM; Zainul Abadin, AFM; Ghosh, Arnob; Motakabber, S. M. A. (Elsevier, 2025)
A reliable and rapid connection between renewable energy system (RES) equipment and components is essential to ensuring a high-quality power supply as RES’s share of the power system grows as a result of emissions decarbonization and sustainability laws. With the quicker and more consistent data bandwidth offered by 6 G, this assessment offers a thorough understanding of the technology’s potential for accelerating RES. The peer-to- peer (P2P) energy trading market, energy management systems (EMS), transportation networks, wireless energy transfer, smart grids, self-healing batteries, and artificial intelligence (AI) weather forecasting are some of the possible uses of 6 G wireless networks for RES’s quicker data processing. This article enumerates the potential uses, practical implementations, and problems of 6 G in the renewable energy sector. It was discovered that while 6 G is a forward-thinking application in the renewable energy sector that will enhance renewable energy’s security, sensory data processing, integration, and connectivity, 6 G still has several technical drawbacks, such as incompatibility with higher power consumption, older devices, and high operating costs. To strike a balance between advances and constraints, future research should concentrate on improving 6 G in RES in terms of power usage, compatibility difficulties, and cost-effectiveness. The 6 G in the RES sector met several critical limitations requiring intensive development, such as security and privacy issues, being vulnerable to cyber-attacks or data blending, which requires advanced hardware support, and requiring ultra-fast communications with low latency. This article provides a vision for 6 G network technology for the RES sector in the future.